MP12: CRYOGLOBULINEMIA IN A PATIENT WITH CHRONIC LYMPHOCYTIC LEUKEMIA (CLL)– A CASE REPORT AND REVIEW OF LITERATURE OF RENAL INVOLVEMENT IN CLL. Issue 3 (23rd February 2016) - Arora, S; Levitan, D; Regmi, N; Sidhu, G; Gupta, R; Nacastri, A; Saggi, SJ; Braverman, A
Abstract : Purpose of Study: We report a case of early stage CLL that caused cryoglobulinemia-related glomerulonephritis (MPGN). This prompted a literature review to identify the incidence and causes of renal disease in patients with CLL. Methods Used: Using a PUBMED search data of cases reported between 1990 and 2014, we selected cases with the following criteria: (1) Clinical and hematologic diagnosis of CLL (2) Evidence of renal insufficiency in association with CLL in the absence of other causes for proteinuria. Summary of Results: Review of the literature revealed that 50 cases of CLL-related nephropathy have been reported, commonly with the nephrotic syndrome (MPGN). IHC staining of the renal biopsies of these patients revealed mostly monoclonal IgG kappa. Many of these were low stage CLL patients and had not been treated. In 68% the renal complications first developed years after the CLL was diagnosed. Most importantly, 65% of all patients' nephropathies responded completely to anti-CLL therapy. Conclusions: We report a rare manifestation of a secretory type of CLL with cryoglobulinemic vasculitis; leading to rapid renal deterioration needing dialysis. Renal damage can be a sequela of early-stage CLL due to its secretory phenotype. Timely recognition of kidney impairment and routine testing of serum or urine proteins in CLL patients is warranted to detect its early transition to a secretory phenotype. We believe that therapeutic intervention in early stage CLL may be effective in the preservation of renal function by removing the secretory phenotypic clone.Abstract MP12 Figure 1